2007
DOI: 10.4049/jimmunol.179.10.7157
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 Administration into the Nostril Alleviates Murine Allergic Rhinitis

Abstract: Type I allergic diseases such as allergic rhinitis are caused by IgE-mediated humoral immune responses, while eosinophils also fulfill important roles in the etiology of IgE-mediated allergy. IL-21 regulates growth, differentiation, and function of T, B, and NK cells, while the production of IgE is also influenced by IL-21. In this study we examined whether IL-21 is capable of controlling IgE-mediated allergic reactions in vivo by using the allergic rhinitis mouse model that was established by repetitive sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 62 publications
4
68
0
1
Order By: Relevance
“…Furthermore, the IL-21 treated mice with AR had significantly reduced serum levels of sIgE and decreased levels of Th2 cytokines (IL-4, IL-5 and IL-13) in the nasal tissues. In addition, the eosinophil selective chemokine-1 and 2 were reduced in IL-4 induced fibroblasts, which inhibited the migration of eosinophils into the nasal tissues (19). Our result indicated there was no significant difference in the serum IL-21 level between AR patients and healthy controls (P>0.05), and IL-21 was not associated with serum sIgE, IL-21, IL-17 and IL-23.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, the IL-21 treated mice with AR had significantly reduced serum levels of sIgE and decreased levels of Th2 cytokines (IL-4, IL-5 and IL-13) in the nasal tissues. In addition, the eosinophil selective chemokine-1 and 2 were reduced in IL-4 induced fibroblasts, which inhibited the migration of eosinophils into the nasal tissues (19). Our result indicated there was no significant difference in the serum IL-21 level between AR patients and healthy controls (P>0.05), and IL-21 was not associated with serum sIgE, IL-21, IL-17 and IL-23.…”
Section: Discussionmentioning
confidence: 57%
“…(Table I). Some insight into the role of IL-21 in allergic responses came from studies showing that exposure to IL-21 resulted in decreased IgE production in an OVA-induced mouse model of allergic rhinitis and in a mouse food allergy model (54,55). In humans, diminution of IgE production has been reported following vaccination with Mycobacterium bovis bacillus Calmette Guerin, BCG (56).…”
Section: Il-21 In Diseasementioning
confidence: 99%
“…We recently found that administration of recombinant mouse IL-21 (rmIL-21) into the nostril of allergic-rhinitis mice significantly inhibited the nasal-allergic reactions as well as IgE CSR in nasal-associated lymphoid tissues (23), although molecular basis for the linkage between IL-21 signal and IgE regulation remains to be elucidated.…”
mentioning
confidence: 99%